Simple technique to fabricate a crown for abutment of an existing cast partial removable denture - Shefali Singla; Amarpreet Kaur; Manu Rathee (Wolters Kluwer Medknow Publications, 2019)
The requirement of full crown restoration for abutments of existing Cast partial removable denture is common. Retrofitting a crown to existing cast partial denture (CPD) clasps and guiding planes is a challenging task. Literature describes various direct, indirect, and direct-indirect techniques to overcome this dilemma. All these involve elaborate steps, necessitating refabrication of CPD or extended clinical adjustment time for ensuring a proper fit that is elusive in most cases and also patient has to do without CPD during laboratory procedure. The recent use of computer-aided design-computer-aided manufacture technology for this purpose is proving to be a promising but expensive option. A simple technique is presented here to generate a blueprint of required final contours to facilitate a fully contoured metal crown to fit under an existing CPD.